Major cardiovascular events in patients with Coronavirus Disease 2019: Experience of a cardiovascular department of Northern Italy. Issue 197 (January 2021) - Bellosta, Raffaello; Pegorer, Matteo Alberto; Bettari, Luca; Luzzani, Luca; Attisani, Luca; Fossati, Alessandro; Consoli, Letizia; Maffeo, Diego; Cuccia, Claudio; Terragnoli, Paolo; Bush, Ruth L.; Piffaretti, Gabriele
Highlights: We report a translational experience of a cardiovascular department facing MACE in COVID-19 patients. Acute arterial events are the real emergency into this COVID-19 pandemic. COVID-19 infection may trigger a hypercoagulable status leading to MACE and high mortality rate. In this COVID-19 outbreak, the adjunct of heparin provides better survival chance independently of the infection-related drug treatment.